(untitled) (Swiss Medical Weekly, 2012)
BACKGROUND: Mortality and morbidity are particularly high in the building industry. The annual rate of non-fatal occupational accidents in Switzerland is 1,133 per 100,000 inhabitants. METHODS: Retrospective analysis of the electronic database of a university emergency centre. Between 2001 and 2011, 782 occupational accidents to construction workers were recorded and analysed using specific demographic and medical keywords. RESULTS: Most patients were aged 30–39 (30.4%). 66.4% of the injured workers were foreigners. This is almost twice as high as the overall proportion of foreigners in Switzerland or in the Swiss labour market. 16% of the Swiss construction workers and 8% of the foreign construction workers suffered a severe injury with ISS >15. There was a trend for workers aged 60 and above to suffer an accident with a high ISS (p = 0.089). CONCLUSIONS: As in other European countries, most patients were in their thirties. Older construction workers suffered fewer injuries, although these tended to be more severe. The injuries were evenly distributed through the working days of the week. A special effort should be made that current health and safety measures are understood and applied by foreign and older construction workers.